Hubungan Antara Tingkat Pengetahuan Kesehatan Rongga Mulut Dan Status Kesehatan Jaringan Periodontal Penderita Diabetes Mellitus Tipe II Terkontrol Pasien Rawat Jalan di RS Pertamina Cilacap - Merdeka, Ayu Rizky Pramestya, Dwi Kurniawati, S.KG, MPH, drg. Fitria Nur Malita Sari (2015)
Background : Diabetes mellitus type II is caused by insulin resistance. Manifestation in the oral condition can be easily found, especially in periodontal tissues. Knowledge of oral health is needed by people with diabetes mellitus as prevention of further complications in the oral health. Aim : This research is aimed to discover the relationship between oral health knowledge level and periodontal health status of outpatients controlled diabetes mellitus type II in PertaminaCilacap Hospital. Method : Kind of this research is observasional analytic with cross sectional design that measure risk factor and impact factor at the same time. Non Random sampling was conducted with Quota Sampling method. The level of oral health knowledge identify using a structured questionnaire, while the periodontal health status identifyusing periodontal disease index (Ramfjord, 1959). Patients diabetes mellitus given a questionnaire about oral health education and after that we chek up for their periodontal health status. The level of oral health knowledge level is on moderate average while the periodontal health status in gingivitis category.. The data were analyzed using Spearman method. Result : Spearman test results showed that the test results have a statistical correlation of - 0.474 with a significance of 0.005. Conclusion : This research concludes that there are relationship between oral health knowledge level and periodontal health status of outpatients controlled diabetes mellitus type II in Pertamina Cilacap Hospital. Where the higher level of oral health knowledge, the health status of the periodontal tissues it's good.